Effectiveness of Honey Dressing on Healing of Diabetic Foot Ulcer: Systematic Review - Farida, Farida; Nizar, Angga Miftakhul; Nurlina, Wa Ode; Agus, Restiyana (International Journal of Psychosocial Rehabilitation, 2020)
Honey is a natural product made by bees by using nectar from flowers. Honey dressing has been widely used for wound dressing, but there are still few studies that review the effectiveness of honey dressing in wound healing in patients. The objective of this study was to evaluate the effectiveness of honey dressing on the healing of wounds based on a literature study. The study was undertaken through a systematic review with the preferred reporting items for systematic reviews and meta-analyses (PRISMA). The literature search was through the Scopus, ProQuest, springer link, EBSCO and Sage databases in the last 10 years (2010-2020) using the keywords: wound care or wound treatment or wound management and honey dressing. There were 15 articles selected from 892 journal articles found. From all the journals analysed there were several comparisons used as a comparison of honey dressing for wound healing in reducing wound surface area, pain level, treatment costs, and increasing patient comfort level. Further research is needed to evaluate honey dressing so that it can be applied more widely as an alternative dressing for diabetic foot ulcers.